METHODOLOGY FOR DEVELOPING STUDENTS' TECHNICAL CREATIVITY BASED ON THE STEAM APPROACH - Ochilova Ozoda Odilovna; Abdullaeva Shoira Isajanovna (PEDAGOGS, 2023)
This article explores the methodology for developing students' technical creativity based on the STEAM approach to teaching physics.